2018
DOI: 10.1093/jn/nxy018
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Replacement of Rice or Potato with Lentils Reduces the Postprandial Glycemic Response in Healthy Adults in an Acute, Randomized, Crossover Trial

Abstract: Replacing half of the AC from high-GI foods with lentils significantly attenuates PBGR in healthy adults; this can contribute to defining a health claim for pulses and blood glucose lowering. This trial was registered at clinicaltrials.gov as NCT02426606.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…It is known that excess rice consumption leads to postprandial glucose spikes that, in turn, lead to compensatory hyperinsulinemia to maintain euglycemia ( 27 , 28 ). Over time, β-cells become exhausted, leading to β-cell failure and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that excess rice consumption leads to postprandial glucose spikes that, in turn, lead to compensatory hyperinsulinemia to maintain euglycemia ( 27 , 28 ). Over time, β-cells become exhausted, leading to β-cell failure and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…While replacing white rice with other cereals, such as wheat or millets, may not be an acceptable option due to taste preferences in some cultures, modifying the diet quality by replacing the staple white rice with less polished brown rice ( 36 ) or healthier varieties of rice may be viable options in countries where highly polished white rice constitutes the bulk (>70%) of the calories in the diet. All legumes, as a class, have a low GI ( 42 ) and, thus, adding legumes to rice not only increases the fiber and protein content but also lowers the GI of the rice-containing meal ( 28 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when incorporating lentils into food with the purpose of delivering low GI properties, a careful evaluation of the processing method and perhaps the storage conditions is warranted. In this study, a large green lentil variety was evaluated; however, a recent study showed that other lentil varieties (e.g., red lentil) have similar efficacies in lowering PPBG [ 44 ]. Although it is important to understand the reasons for variations in PPBG among different food types, it is clear that the reformulation of meals by replacing high glycemic food ingredients like potato with lentil is a useful approach for managing persons with impaired glycemic control and promoting healthy eating [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…84 Another study focused on the replacement of AC in rice or potatoes with lentils on postprandial glycemic response in 24 healthy adults. 85 Results showed that glucose maximum concentration (Cmax) and AUC were significantly decreased by replacing half of the AC from rice or potato with large green (P = 0.057 for rice AUC), small green and red lentils; and insulin Cmax and AUC were significantly decreased by replacing half of the potato AC with all 3 lentil types. 85 Pulses processed in various ways (ie, boiled, pureed, powdered, flour, fractions) have also been examined for their glycemic effects in healthy adults (Supplemental Table 2).…”
Section: Effect Of Pulse Consumption On Glycemic Response In Adults Wmentioning
confidence: 99%